2016
DOI: 10.3390/nu8080471
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Time to Achieve Full Enteral Feeding in Human Milk-Fed and Formula-Fed Preterm Infants: Systematic Review and Meta-Analysis

Abstract: Probiotics have been linked to a reduction in the incidence of necrotizing enterocolitis and late-onset sepsis in preterm infants. Recently, probiotics have also proved to reduce time to achieve full enteral feeding (FEF). However, the relationship between FEF achievement and type of feeding in infants treated with probiotics has not been explored yet. The aim of this systematic review and meta-analysis was to evaluate the effect of probiotics in reducing time to achieve FEF in preterm infants, according to ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…In the current cohort study, we noted a promoting effect of probiotics on weight gain and growth velocities in HM-fed infants. Previous studies revealed inconsistent results that were not necessarily adjusted for the type of feeding [27][28][29][30]. A meta-analysis of 15 studies including 3751 infants <32 weeks and <1500 g birth weight demonstrated no significant effects of probiotics on weight gain [31].…”
Section: Discussionmentioning
confidence: 98%
“…In the current cohort study, we noted a promoting effect of probiotics on weight gain and growth velocities in HM-fed infants. Previous studies revealed inconsistent results that were not necessarily adjusted for the type of feeding [27][28][29][30]. A meta-analysis of 15 studies including 3751 infants <32 weeks and <1500 g birth weight demonstrated no significant effects of probiotics on weight gain [31].…”
Section: Discussionmentioning
confidence: 98%
“…In a review on the effects of a variety of immunonutrients in the prevention of necrotizing enterocolitis [35], the authors gathered sufficient data supporting supplementation of infant formulae with probiotics. Several meta-analyses combined these randomized controlled trials and observational studies demonstrated that the use of probiotics was beneficial for the prevention of severe necrotizing enterocolitis, late-onset sepsis, and all-cause mortality in very-low-birth-weight infants, as well as the time to achieve full enteral feeding in preterm infants [36][37][38]. By contrast, no differences were observed in a multicenter study involving 1315 preterm newborns fed with a hydrolyzed formula supplemented and nonsupplemented with the probiotic Bifidobacterium breve BBG-001 [39]; the results of this trial provide no evidence of benefit of this probiotic intervention in reducing late-onset sepsis and necrotizing enterocolitis or death.…”
Section: Prevention and Treatment Of Infant Disordersmentioning
confidence: 99%
“…Preterm infants fed donor milk had gut microbiomes that more closely resembled infants fed their mother's own milk compared with formula fed infants (Parra‐Llorca et al, ). In addition, some groups have tested the viability of “spiking” donor milk with infants' own mothers milk to inoculate the infants with a personalized microbiome (Cacho et al, ), a concept similar to a recent push to include probiotics in infant formula (Aceti et al, ; Cavallaro, Villamor‐Martínez, Filippi, Mosca, & Villamor, ; Mugambi, Musekiwa, Lombard, Young, & Blaauw, ; Rautava et al, ; Villamor‐Martínez et al, ). These interventions showcase the importance of breastfeeding, or in lieu of breastfeeding, a diet reflecting the myriad of components maternally transferred that support the development of the offspring's immune system and shape gut homeostasis during early life.…”
Section: Nongenetic Inherited Influences Directly On the Immune Systemmentioning
confidence: 99%